2012
DOI: 10.1007/s00705-012-1333-8
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of a new strain of grapevine leafroll-associated virus 3 in South Africa

Abstract: The complete genome sequences of two newly identified genetic variants of grapevine leafroll-associated virus 3 (GLRaV-3) are described. Two isolates, GH11 (18671 nt) and GH30 (18576 nt) were sequenced and found to be less than 70 % similar to other South African GLRaV-3 variants. The genome organization of GH11 and GH30 is similar to that of previously described GLRaV-3 isolates. However, no corresponding open reading frame 2 (ORF2) could be identified. Phylogenetic analysis indicates that GH11 and GH30 clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…Gouveia and Nolasco (2012) found differences among GLRaV-3 variants in the suppressing activity of the p19.7 silencing suppressor, suggesting that variants may differ in their ability to overcome host plant defenses. The two variants tested in this study share <70% nucleotide sequence similarity, and their predicted protein amino acid sequences are >10% different from each other (Bester et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Gouveia and Nolasco (2012) found differences among GLRaV-3 variants in the suppressing activity of the p19.7 silencing suppressor, suggesting that variants may differ in their ability to overcome host plant defenses. The two variants tested in this study share <70% nucleotide sequence similarity, and their predicted protein amino acid sequences are >10% different from each other (Bester et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…GLRaV genomes range from 13,626 nucleotides (nt) encoding six open reading frames (ORFs) in GLRaV-4 strain Car (1) to 18,671 nt with 12 ORFs in GLRaV-3 (21). Compared with other monopartite members of the family Closteroviridae, some genome characteristics are distinct and seemingly unique to the GLRaVs.…”
Section: Figurementioning
confidence: 99%
“…Studies on genetic diversity of GLRaV-1, -2, and -3 have indicated the presence of genetically diverse but closely related variants in several grapevine-growing regions (3,20,30,70,84,146,160). In the case of GLRaV-3, the presence of seven possible variant groups has been reported in different cultivars and vineyards worldwide based on phylogenetic analysis of full-length CP gene sequences (105).…”
Section: Taxonomy Genome Organization and Diversity Of Glravsmentioning
confidence: 99%